Anatomical relations of the superficial sensory branches of the radial nerve: a cadaveric study with clinical implications - Samarakoon, Lasitha B (BioMed Central, 2011)
BACKGROUND: Anatomically, it is difficult to give a systematic description of the superficial branch of the radial nerve (SBRN). Our aim was to describe the exact relationship of the SBRN to fixed bony points of radial styloid and Lister's tubercle, and to the cephalic vein. We also compared our data with other international studies. METHODS: The study was a descriptive anatomical study. Twenty-five forearms were dissected. Measurements were made from predefined fixed reference points. RESULTS: The mean distance to the point of emergence of the nerve from the radial styloid was 8.54 cm (SD = 1.32). The nerve branched at a mean distance of 5.57 cm (SD = 1.43) from the radial styloid. The mean distance to the point where the most medial and most lateral branches of the nerve crossing the wrist joint, measured from the Lister's tubercle were 2.51 cm (SD = 0.53) and 3.90 cm (SD = 0.64). In 17 specimens(68%) cephalic vein crossed the SBRN superficially once. Mean distance from the radial styloid to the most distal point where the vein crossed the nerve was 5.10 cm. Diffefrence between mean distance to the point of emergence and branching point, when compared with other international studies were not statistically significant. (P value > 0.05) CONCLUSIONS: We recommend avoiding transverse incisions in the snuffbox region between 2.51 cm and 3.90 cm from the Listers tubercle. We also recommend avoiding cannulation of the cephalic vein in the distal forearm.